The Leader Position of Mesenchymal Cells Expressing N-Cadherin in the Collective Migration of Epithelial Cancer - Inés Saénz-de-Santa-María; Lucía Celada; María-Dolores Chiara (Cells, 2020)
Understanding how heterogeneous cancer cell populations migrate collectively is of paramount importance to arrest metastasis. Here, we applied 3D culture-based approaches for in vitro modeling of the collective migration of squamous carcinoma cells and examine the impact of epithelial and mesenchymal cell interactions on this type of migration. We show that both mesenchymal N-cadherin-expressing cancer cells and cancer-associated fibroblasts cooperate in collective migration of epithelial cancer cells by leading their collective migration. This was consistent with the observed distribution of E-cadherin/N-cadherin in the human carcinoma tissues of head and neck. The presence of “leader” mesenchymal cancer cells or “leader” fibroblasts was significantly associated with metastasis development, recurrent disease and low overall disease survival in head and neck squamous cell carcinomas (HNSCC). In silico analysis of independent public datasets revealed that increased N-cadherin expression in the heterogeneous cancer tissues is associated with disease progression not only in HNSCC but also in other prevalent tumors, such as colorectal, breast and lung cancer. Collectively, our data highlight the importance of mesenchymal cells in collective cell migration and disease progression, findings that may have a broad significance in cancer, especially in those in which aberrant N-cadherin expression negatively impacts disease survival.